2021
DOI: 10.1186/s13045-021-01206-y
|View full text |Cite
|
Sign up to set email alerts
|

A novel CD123-targeted therapeutic peptide loaded by micellar delivery system combats refractory acute myeloid leukemia

Abstract: Acute myeloid leukemia (AML) is a common malignant heterogeneous hematopoietic disease with very low average 5-year survival rate due to the refractory feature and high rate of relapse. CD123 is highly expressed on multiple types of AML cells, especially leukemia stem cells, and closely associated with the poor prognosis of AML. Aiming to meet the urgent demand to targeted therapeutics for the refractory AML patients, herein we synthesize a CD123 antagonistic peptide (PO-6) loaded in nanomicelles (mPO-6), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 18 publications
(11 reference statements)
0
23
0
Order By: Relevance
“…It has been well-documented that IL-3 can trigger the activation of NF-κB by the signaling pathway of STATs and PI3K/AKT, which mediated activation of multiple genes linked to cell proliferation and anti-apoptosis expressions. ,, It has been known that m PO-6 could competitively bind to the extracellular N-terminal domain of CD123 on the CD123 + AML cells, which is the important site for influencing IL-3-mediated signaling pathways . In this study, experimental results showed that m PO-6 played a CD123 antagonistic role to the MOLM-13 cells by inhibiting IL-3-mediated the phosphorylation of STAT5 and PI3K as well as the activation of NF-κB in the nucleus (Figure A,B).…”
Section: Resultsmentioning
confidence: 73%
See 3 more Smart Citations
“…It has been well-documented that IL-3 can trigger the activation of NF-κB by the signaling pathway of STATs and PI3K/AKT, which mediated activation of multiple genes linked to cell proliferation and anti-apoptosis expressions. ,, It has been known that m PO-6 could competitively bind to the extracellular N-terminal domain of CD123 on the CD123 + AML cells, which is the important site for influencing IL-3-mediated signaling pathways . In this study, experimental results showed that m PO-6 played a CD123 antagonistic role to the MOLM-13 cells by inhibiting IL-3-mediated the phosphorylation of STAT5 and PI3K as well as the activation of NF-κB in the nucleus (Figure A,B).…”
Section: Resultsmentioning
confidence: 73%
“…In the current work, the AML mouse model was established by intravenously injecting AE and CKIT D816V cells into C57Bl/6 mice followed by X-ray irradiation at a dose of 450 cGy. The AML mice are refractory because they are not able to benefit from cytarabine, one of the first-line chemotherapeutics due to the gene mutation feature . We examined whether m PO-6 could prolong the survival of the mice following the schematic regimens (Figure A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…CD123 is highly expressed on AML blasts and leukemic stem cells (LSCs) and demonstrates only a moderate expression on normal HSCs, suggesting that CD123 is a promising target antigen [ 190 ]. SIRPα receptors on macrophages interact with CD47 to inhibit phagocytosis.…”
Section: Cd47/sirpα-targeted Bispecific Antibodies (Bsabs)mentioning
confidence: 99%